Cover Picture: Influence of Chromophore Length and Acceptor Groups on the Optical Properties of Rigidified Merocyanine Dyes (ChemPlusChem 2/2014). Issue 2 (20th December 2013) - Kreß, Katharina Christina; Fischer, Thomas; Stumpe, Joachim; Frey, Wolfgang; Raith, Melanie; Beiraghi, Omid; Eichhorn, S. Holger; Tussetschläger, Stefan; Laschat, Sabine
Abstract : The cover picture shows three rigidified "push–pull" dyes with variations in the length of the chromophore. Upon excitation within the UV/Vis region, electronic transitions take place. On the left are the calculated HOMO energies and on the right are the corresponding LUMO energies, with inverted nodal planes shown. Systematic experimental and theoretical investigations of the absorption and emission spectra of dyes that vary in either chromophore length or acceptor unit were carried out. The consequent results provide information on structure–property relationships, which could be used to tailor potentially functional dyes for widespread applications. Further details can be found in the Full Paper onpage 223 by Sabine Laschat, Holger Eichhorn, and co‐workers.